Gramatical Typology and Pivot System of Mandailing Language - Rezky Khoirina Tarihoran; Mulyadi Mulyadi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Mandailing language is a syntax that concerns the identification of coherence in complex sentences by identifying its development in the language spoken in the southern plains of Sumatra. This study uses qualitative description, which includes the depiction, discovery of patterns, and formulation in BM which is associated with the typology system. The method used is the agih method. This method used Replacing technique, and prostrate techniques in agih performed against the coordinate, subordinate, adverbial clause, and construction with infinite verbs. Based on the research, the language structure adopted by BM uses a language structure that adheres to the SVO or VOS system with the noun phrase "controller" determining the higher clause and the FN "pivot" determinded the lower clause.